Effect of mode of delivery and background noise on speech characteristics of talkers in a classroom environment. Issue 2 (June 2020) - Subramaniam, Nithya; Ramamurthy, K
Global and acoustic–phonetic correlates of speech intelligibility are important measures of talker intelligibility. Speech characteristics have been evaluated using speech samples that involve reading pre-administered passages under controlled environments. In classrooms, lecturing is the mode of speech delivery. The presence of noise from ceiling fans and other external noise hinder the speech communication process. This study evaluated the talkers' speech characteristics utilizing recordings from graduate students under reading and lecturing modes and in the presence and absence of noise generated by ceiling fans. The acoustical conditions under which talkers delivered their speech were characterized using octave band U50 values. Global and acoustic–phonetic correlates of talker intelligibility were measured and the variation in correlates of speech intelligibility was statistically analyzed. The results revealed that talkers significantly modified their speech characteristics relevant to intelligibility across modes of speech delivery and in the presence of noise. Fundamental frequency measures such as F0-mean and F0-SD and durational measures such as speech and pause rates were all found to be higher for lecture mode of delivery. Talkers showed similar vowel-articulatory changes under the two modes of delivery. When lecturing in the presence of noise, talkers significantly reduced the length of pauses and also utilized a combination of vowel-articulatory strategies to overcome the presence of noise. The results suggest the need to investigate talkers' speech adaptation in real classroom environments in terms of correlates of speech intelligibility and to reconsider classroom acoustical guidelines in view of both listener and talker intelligibilities.